Ceftazidime/avibactam resistance is associated with PER-3-producing ST309 lineage in Chilean clinical isolates of non-carbapenemase producing Pseudomonas aeruginosa - Soto, Katherine D.; Alcalde-Rico, Manuel; Ugalde, Juan A.; Olivares-Pacheco, Jorge; Quiroz, Valeria; Brito, Bárbara; Rivas, Lina M.; Munita, José M.; García, Patricia C.; Wozniak, Aniela (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Ceftazidime/avibactam (CZA) is indicated against multidrug-resistant Pseudomonas aeruginosa, particularly those that are carbapenem resistant. CZA resistance in P. aeruginosa producing PER, a class A extended-spectrum β-lactamase, has been well documented in vitro. However, data regarding clinical isolates are scarce. Our aim was to analyze the contribution of PER to CZA resistance in non-carbapenemase-producing P. aeruginosa clinical isolates that were ceftazidime and/or carbapenem non-susceptible. Methods Antimicrobial susceptibility was determined through agar dilution and broth microdilution, while blaPER gene was screened through PCR. All PER-positive isolates and five PER-negative isolates were analyzed through Whole Genome Sequencing. The mutational resistome associated to CZA resistance was determined through sequence analysis of genes coding for PBPs 1b, 3 and 4, MexAB-OprM regulators MexZ, MexR, NalC and NalD, AmpC regulators AmpD and AmpR, and OprD porin. Loss of blaPER-3 gene was induced in a PER-positive isolate by successive passages at 43°C without antibiotics. Results Twenty-six of 287 isolates studied (9.1%) were CZA-resistant. Thirteen of 26 CZA-resistant isolates (50%) carried blaPER. One isolate carried blaPER but was CZA-susceptible. PER-producing isolates had significantly higher MICs for CZA, amikacin, gentamicin, ceftazidime, meropenem and ciprofloxacin than non-PER-producing isolates. All PER-producing isolates were ST309 and their blaPER-3 gene was associated to ISCR1, an insertion sequence known to mobilize adjacent DNA. PER-negative isolates were classified as ST41, ST235 (two isolates), ST395 and ST253. PER-negative isolates carried genes for narrow-spectrum β-lactamases and the mutational resistome showed that all isolates had one major alteration in at least one of the genes analyzed. Loss of blaPER-3 gene restored susceptibility to CZA, ceftolozane/tazobactam and other β-lactamsin the in vitro evolved isolate. Discussion PER-3-producing ST309 P. aeruginosa is a successful multidrug-resistant clone with blaPER-3 gene implicated in resistance to CZA and other β-lactams.